Lessons learnt from the first vertical slice of the CMS Outer Tracker. (1st January 2023) - Fedi, G.; Fiorendi, S.; Holmberg, M.; Howard, A.; Iles, G.; Monk, D.; Pesaresi, M.; Whalen, K.; ,
Abstract: A vertical slice of the CMS Outer Tracker has been tested at the tracker integration facility and at the M2 muon beam facility at CERN. It includes the final prototype of the 2S module with an optical link to the back-end ATCA system. The performance of the system will be described, including cooling limits of racks, robustness of 25 Gbit/s trigger optical links, and readiness of firmware.